Secondary school students’ perspectives on supports for overcoming school attendance problems: a qualitative case study in Germany - Enderle, Chiara; Kreitz-Sandberg, Susanne; Backlund, Åsa; Isaksson, Joakim; Fredriksson, Ulf; Ricking, Heinrich (Frontiers in Education, 2024)
School attendance problems (SAPs) affect both young learners’ education and development. There is a need to better understand what supports are necessary to overcome and prevent SAPs from students’ viewpoints. The aim of the current study is to explore students’ perspectives on what challenges they faced, and what they perceived as helpful in overcoming attendance challenges on their pathways towards completing their education. We conducted interviews with students (n = 9) in a local comprehensive school (Stadtteilschule) in the city-state Hamburg in Germany. Students were in their final year before obtaining a certificate that qualifies them for possible admission to post-secondary education. Data was analyzed using qualitative content analysis. Findings show that students experienced complex challenges to school attendance associated with emotional distress, negative school experiences and reduced well-being. Our findings point to common protective mechanisms in students’ perceptions of what helped them overcome SAPs. The key drivers of school attendance are located in students and their social contexts, encompassing personal resilience, supportive relationships in school and social environment. Based on students’ views, we present a model that illustrates the interconnectedness of perceived challenges and supports in the function of risk and protective factors moving across ecological systems in the development of SAPs. We highlight how these areas can guide prevention and intervention to support students in successfully completing their education and transitioning into multiple post-secondary pathways.